2002
DOI: 10.1523/jneurosci.22-04-01328.2002
|View full text |Cite
|
Sign up to set email alerts
|

Activity Deprivation Reduces Miniature IPSC Amplitude by Decreasing the Number of Postsynaptic GABAAReceptors Clustered at Neocortical Synapses

Abstract: Maintaining the proper balance between excitation and inhibition is necessary to prevent cortical circuits from either falling silent or generating epileptiform activity. One mechanism through which cortical networks maintain this balance is through the activity-dependent regulation of inhibition, but whether this is achieved primarily through changes in synapse number or synaptic strength is not clear. Previously, we found that 2 d of activity deprivation increased the amplitude of miniature EPSCs (mEPSCs) on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

32
367
5
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(405 citation statements)
references
References 46 publications
32
367
5
1
Order By: Relevance
“…In support, previous evidence demonstrated that variations in both the GABA content of vesicles (Frerking et al, 1995) and the number of postsynaptic GABA A receptors (Nusser et al, 1997(Nusser et al, , 1998 determine mIPSC amplitude. Moreover, a reduction in both the staining intensity of GAD-65 and synaptic GABA A receptors was previously observed in cultured cortical neurons after activity blockade (Kilman et al, 2002).…”
Section: Activity-dependent Scaling Of Gabaergic Synapse Strengthmentioning
confidence: 58%
See 1 more Smart Citation
“…In support, previous evidence demonstrated that variations in both the GABA content of vesicles (Frerking et al, 1995) and the number of postsynaptic GABA A receptors (Nusser et al, 1997(Nusser et al, , 1998 determine mIPSC amplitude. Moreover, a reduction in both the staining intensity of GAD-65 and synaptic GABA A receptors was previously observed in cultured cortical neurons after activity blockade (Kilman et al, 2002).…”
Section: Activity-dependent Scaling Of Gabaergic Synapse Strengthmentioning
confidence: 58%
“…Neuronal activity can also regulate the strength of inhibitory synapses (Kilman et al, 2002), although the signals that mediate this process are unknown. Similar to excitatory synapses, BDNF is an attractive candidate to scale the strength of inhibitory synapses in response to long-term alterations in neuronal activity.…”
Section: Introductionmentioning
confidence: 99%
“…Most importantly, they demonstrate that conductive impairment at a very early age may induce re-organization within auditory cortex, where CHL occurring later in development may promote a different mode or temporal sequence of cortical re-organization. These different modes may include potential plastic changes (e.g., Irvine, 2007) or perturbed expression of neurotransmitters or their receptors (e.g., Cherubini et al, 1991;Gao et al, 1999;Kilman et al, 2002;Yu et al, 2006). Regardless of the underlying mechanism, our main observation remains that in response to low frequency sound stimulation, CHL, but not CA, decreases activity in auditory cortex.…”
Section: Developmental Effects Of Unilateral Chlmentioning
confidence: 87%
“…Only a few experimental studies have been done on inhibitory plasticity (Kilman et al 2002;Woodin et al 2003;Haas et al 2006;Wenner 2011), and theoretical modeling is almost nonexistent (Vogels et al 2011). It would be important to study the advantages and possibilities of inhibition so that more links to memory and learning could be made.…”
Section: Open Questionsmentioning
confidence: 99%